CLASSICAL DANCE IN CONTEMPORARY INDIA: TRADITION, TRANSFORMATION, AND INSTITUTIONAL SUPPORT - Rawat, Akash Kumar; Shivangi; Upadhyaya, Nandini (ShodhKosh: Journal of Visual and Performing Arts, 2026)
One of the most important representations of India’s intangible cultural heritage is Indian classical dance. It makes the connection between modern social reality and classical aesthetic theory. This article explains the historical development of Indian classical dance using institutional sources, contemporary studies, and classical treatises. The study covers the features of major forms, the function of institutions and cultural policy, modern advances, and important issues and opportunities. Article analysis Bharatanatyam, Kathak, Odissi, Kuchipudi, Manipuri, Kathakali, Mohiniyattam, and Sattriya. These classical dances continue to exist as living traditions that balance continuity and change. It makes the case that inclusive cultural education, morally grounded innovation, and consistent institutional support are critical to the long-term viability of Indian classical dance in the globalized, digital age.